2017
DOI: 10.1016/j.precamres.2017.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Western Paraná suture/shear zone and the limits of Rio Apa, Rio Tebicuary and Rio de la Plata cratons from gravity data

Abstract: We present a new gravity map between 45°-70° W and 5°-40° S integrating open source terrestrial gravity data of Argentina with the South American Gravity Model 2004 (SAGM04), a 5 min-arc resolution gravity model. The Bouguer anomaly map reveals a 2,000 km long linear gravity feature from 15° S to 30° S at longitude 55° W, with a steep horizontal gradient separating two gravity domains. The eastern domain is the Paraná basin, with NE-SW trending Bouguer anomalies of-80 mGal in average. The western domain compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 88 publications
(118 reference statements)
6
38
1
Order By: Relevance
“…4. Does the deep resistivity structure support or help improve our understanding of the previously observed seismic and potential field anomalies (Chaves et al, 2016;Dragone et al, 2017;VanDecar et al, 1995) as well as the heat flow anomalies (e.g., Hamza et al, 2005;Hurter & Pollack, 1996) in the study area?…”
Section: 1029/2017gc007314mentioning
confidence: 89%
See 3 more Smart Citations
“…4. Does the deep resistivity structure support or help improve our understanding of the previously observed seismic and potential field anomalies (Chaves et al, 2016;Dragone et al, 2017;VanDecar et al, 1995) as well as the heat flow anomalies (e.g., Hamza et al, 2005;Hurter & Pollack, 1996) in the study area?…”
Section: 1029/2017gc007314mentioning
confidence: 89%
“…In (a)–(f), the Paraná axial anomaly and coastal mantle anomaly (CMA) are shown to peak and fade out at different depths. In (c), the inset black box, red polygon shows the Western Paraná Suture and the dashed black line is another suture, both proposed by Dragone et al (). A possible offset to feature CMA is shown in (f) by the black dashed lines.…”
Section: Mt and Gds 3‐d Inversion Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact mechanism for the extrusion of the magma is not known in detail; it could be related to a central source in the middle of the Paraná Basin or multiple sources spread throughout the entire province. Gravity data show a NE‐SW trending Bouguer high along the central axis of the Paraná Basin (e.g., Dragone et al, ), which had been interpreted as due to magmatic underplating in the lower crust related to the extrusion process. However, attempts to detect an underplated lower crust by seismic methods (An & Assumpção, , ; Julià et al, ; Shirzad et al, ) have not identified significantly higher velocities beneath the Paraná Basin.…”
Section: Geological Settingmentioning
confidence: 99%